"Crossing the River by Feeling the Gold": The Asian Infrastructure Investment Bank and the Financial Support to the Belt and Road Initiative. Issue 5 (September 2017) - Gabusi, Giuseppe
Abstract: China's Belt and Road Initiative (BRI) is, above all, a connectivity project. As connectivity requires financial support, in the past few years China has undertaken several institution‐building activities at the national and international level, mainly in the financial and economic sector, showing a new propensity to influence global economic governance. In particular, the establishment of the Asian Infrastructure Investment Bank (AIIB) has drawn attention worldwide. How does this institution‐building process connect with BRI? Are these institutions just a vehicle for exporting China's capital and overcapacity, or do they signal a potential wider challenge to the post‐World War II liberal international order? By analyzing the first loans approved by the bank, the present paper argues that far from representing a China‐led challenge to the Western‐led liberal order, the AIIB, while promoting Chinese commercial and geopolitical interests, shows the resilience of the global financial regime created by the West.